Outcome of Midline Posterior Cranial Fossa Tumor Surgery with Preoperative Ventriculo - Peritoneal (V-P) Shunt in Children - MR, Amin; KMT, Islam; ABM, Hossain; M, Haque (Archives of Clinical and Medical Case Reports, 2024)
Introduction: Pediatric patients with midline posterior cranial fossa tumors present with features of raised intracranial pressure due to development of hydrocephalus. Due to the big size tumour and lack of facility we did Ventriculoperitoneal shunt before definitive surgery for all patients. Material and Methods: This cross-sectional experimental study was carried out on 55 consecutive patients with midline posterior cranial fossa brain tumors with obstructive hydrocephalus with age ranged from 3 to 15 years got admitted in the Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University from March 2021 to April 2023. We did preoperative ventriculoperitoneal shunt before definitive surgery but didn’t do the Endoscopic third ventriculostomy. Results: In this study, the age of the patients was 3-15 years, the mean age was 9.47+_3.18 and the peak incidence was 11-15 years which was 20(36.36%). Majority of the patients was male (56%), male female ratio was 1.27:1. Most of the children were presented with headache 51(92.73%) followed by papilloedema 47(85.45%), vomiting 46(83.64%), gait disturbance 37(67.27%), diminution of vision 31(56.36%), swallowing difficulty 12(21.82%), cranial nerve palsy 12(21.82%). 19 patients developed postoperative complications among them 15(27.27%) was meningitis followed by wound infection 7(12.73%), pseudomeningocele 8(14.55%), csf leakage 4(7.27%), hydrocephalous 3(5.45%). Logistic regression analysis was non-significant statistically in my study. Discussion and Conclusion: In conclusion we found satisfactory outcome of doing pr-operative VP Shunt in posterior fossa midline tumor causing obstructive Hydrocephalus in children, however major postoperative complications were development of hydrocephalus, CSF leak, pseudo meningocele, wound infection and meningitis. Future prospective studies with sufficient sample size are warranted to reach a definitive conclusion.